A free energy landscape perspective on the nature of collective diffusion in amorphous solids. (15th September 2018) - Wang, Yun-Jiang; Du, Jun-Ping; Shinzato, Shuhei; Dai, Lan-Hong; Ogata, Shigenobu
Abstract: The nature of collective diffusion in amorphous solids is in strong contrast with diffusion in crystals. However, the atomic-scale mechanism and kinetics of such collective diffusion remains elusive. Here the free energy landscape of collective diffusion triggered by single atom hopping in a prototypical Cu50 Zr50 metallic glass is explored with well-tempered metadynamics which significantly expands the observation timescale of diffusion at atomic-scale. We clarify an experimentally suggested collective atomic diffusion mechanism in the deep glassy state. The collective nature is strongly temperature-dependent. It evolves from string-like motion with only several atoms to be large size collective diffusion at high temperature, which can promote the atomic transport upon glass transition temperature. We also clarify the apparent diffusivity is dominated by the highest free energy barrier of atomic diffusion among widely distributed free energy barriers due to the dynamic heterogeneity of metallic glass, which suggests the sequential nature of diffusion is a proper assumption to the metallic glasses with dynamic heterogeneity. The temperature and pressure dependence of diffusion free energy landscape are further quantified with activation entropy, (19.6 ± 2.5) k B, and activation volume, (7.9 ± 3.4) Å 3, which agree quantitatively with experiments. Laboratory timescale simulations of atomic diffusion brings physical insights into the unique atomic motion mechanism in non-crystalline materials. Graphical abstract: The collection diffusion mechanism and the related free energy surface of amorphous solids is explored with accelerated molecular dynamics which significantly expands the observation time of diffusion process with atomic resolution. The diffusion patterns are recognized over very wide temperature range from deep glassy state to glass transition that has never been achieved via the conventional atomistic simulations. The string-like motion and its temperature dependence are discussed in terms of free energy landscape. Image 1